Law, religion and freedom. An approach in the context of globalization (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Religion represents one of the benchmarks for the Romanian communities abroad. Each representative of our society becomes basically a symbol and a promoter of Romanism in the host country. Therefore, regardless of faith or belief, the contribution of each citizen or friend of Romania in promoting a real and honest image of our country abroad is very valuable.